Battery energy storage system modeling: A combined comprehensive approach. (February 2019) - Dubarry, Matthieu; Baure, George; Pastor-Fernández, Carlos; Yu, Tung Fai; Widanage, W. Dhammika; Marco, James
Highlights: New modular battery pack modeling approach. The model considers cell-to-cell variations at the initial stage and upon aging. New parameter for imbalance prediction: degradation ratio charge vs. discharge. Abstract: Battery pack modeling is essential to improve the understanding of large battery energy storage systems, whether for transportation or grid storage. It is an extremely complex task as packs could be composed of thousands of cells that are not identical and will not degrade homogeneously. This paper presents a new approach toward battery pack modeling by combining several previously published models into a comprehensive framework. This work describes how the sub-models are connected, their basic principles, what adjustments were necessary, and what new parameters needed to be introduced. Overall, this paper introduces an open modular framework for future work on, among others, the impact of cell-to-cell variations, inhomogeneous degradation, SOC and SOH tracking, balancing and performance forecast.